ДОЗВОЛЕНОСТ НА РЕВИЗИЈА ВО ПАРНИЧНАТА ПОСТАПКА НИЗ ПРАКТИКАТA НА ВРХОВНИОТ СУД НА РЕПУБЛИКА СЕВЕРНА МАКЕДОНИЈА - Татјана Зороска Камиловска, Милка Ракочевиќ (Pravni fakultet Sveučilišta u Splitu, 2019)
In Macedonian civil procedure the second appeal is regulated as an extraordinary legal remedy. In civil cases it is the only legal remedy to initiate proceedings before the Supreme Court as the highest judicial authority. Regarding its admissibility, the second appeal always appears as a limited legal remedy. Under the current legislative solution, according to the Macedonian CPA, a distinction is made between two types of second appeal that the procedural theory recognizes as ordinary and extraordinary second appeal. There is a difference regarding the criteria for their admissibility as legal remedies. The article discusses the specifics of the current legal regime of the ordinary and extraordinary second appeal, with reference to the practice of the Supreme Court on certain issues regarding the possibility of filing this legal remedy.
Keywords: civil procedure, legal remedies, ordinary second appeal (revision), extraordinary second appeal (revision)